US monetary shocks and global stock prices - Laeven, Luc; Tong, Hui (Journal of Financial Intermediation, 2012)
This paper studies how US monetary policy affects global stock prices. We find that global stock prices respond strongly to changes in US interest rates, with stock prices increasing (decreasing) following unexpected monetary loosening (tightening). This impact is more pronounced for sectors that depend on external financing, and for countries whose domestic monetary policy is more aligned with that of the United States. Using investment data, we present results consistent with this effect operating primarily through changes in risk premiums as opposed to changes in expected returns. These findings suggest that US monetary shocks affect firms’ stock prices by influencing local interest rates, and offer new evidence that financial frictions play an important role in the transmission of monetary policy to the real economy.